How Islamic Values and Political Trust Shape Perceptions of Social Development: Evidence from Urban Zanzibar - Nassir Massoud Nassor (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
Studies on Islamic governance extensively highlight the integration of religious values into contemporary administrations. However, theoretical explanations regarding how these values interact with political trust in constructing social development perceptions at the local level remain limited. This study analyzes the significance of Islamic values, political trust, and governance quality in shaping social development perceptions among urban political actors in Zanzibar. Employing an exploratory qualitative design, data were gathered through semi-structured in-depth interviews with 22 political actors from CCM, ACT-Wazalendo, and CHADEMA, and analyzed using thematic analysis. The findings reveal that social development perceptions are not monolithic, but rather a dialectical construction driven by governance quality, political trust, and the internalization of axiological Islamic values—specifically amanah (trustworthiness), ‘adl (justice), shura (consultation), and maslahah (public interest). Crucially, this study offers a distinct theoretical contribution by redefining the function of these religious values; rather than operating merely as static normative doctrines, they transform into active evaluative instruments and empirical frameworks for legitimacy used by political actors to measure bureaucratic performance and development trajectories within a contemporary urban Muslim society.